Ethical issues in ophthalmic practice and the ways to monitor ethics - Reddy, Sagili Chandrasekhara (Nepalese Journal of Ophthalmology, 2014)
DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10758 Nepal J Ophthalmol 2014; 6 (2): 3-5